Determinants of Financial Literacy, Digital Literacy and Consumer Confidence Level Mediated by Fintech Literacy on Retail Industry Growth in Indonesia - Sapta Rini, Anggarwati; Mukti Soma, Abdul (Publisher Cv. Inara, 2025)
This study evaluates how financial literacy, digital literacy, and consumer confidence influence retail industry growth in Indonesia, emphasizing the mediating role of fintech literacy. In the era of industry 4.0, technology, especially fintech, has transformed conventional financial business models into digital ones, accelerating transactions and financial inclusion. The Covid-19 pandemic has further driven digitalization, although it has posed major challenges for the retail industry. This study aims to determine the actual impact of the development of fintech applications including the influence of financial literacy, digital literacy and consumer confidence levels on the development or growth of retail in Indonesia. This study uses a quantitative method with a focus on analysing the relationship between financial literacy, digital literacy, and consumer confidence levels on the growth of the retail industry, both directly and through fintech literacy mediation. The data used are primary data that include information on financial literacy, digital literacy, consumer confidence levels, fintech literacy, and retail growth. Data collection uses a Likert scale questionnaire with a scale of one to five for each variable. The analysis was carried out using multiple linear regression to identify direct relationships between variables and structural equation modelling (SEM) to comprehensively evaluate the influence of fintech mediation. This study shows that financial literacy has a positive and significant influence on retail growth without fintech literacy mediation. However, it does not have a significant effect on retail growth with fintech literacy mediation. In contrast to digital literacy, where digital literacy has a significant and positive effect on retail growth with fintech literacy mediation. While without fintech literacy, this variable does not have a significant effect on retail growth. The level of consumer confidence has a positive and significant effect on retail growth directly and with fintech literacy mediation.